Asymmetric Returns: The Future of Active Asset Management - M.Ineichen Alexander (Wiley, 2006)
In Asymmetric Returns, financial expert Alexander Ineichen elevates the critical discussion about alpha versus beta and absolute returns versus relative returns. He argues that controlling downside volatility is a key element in asset management if sustainable positive compounding of capital and financial survival are major objectives. Achieving sustainable positive absolute returns are the result of taking and managing risk wisely, that is, an active risk management process where risk is defined in absolute terms and changes in the market place are accounted for. The result of an active risk management process-when successful-is an asymmetric return profile, that is, more and higher returns on the upside and fewer and lower returns on the downside. Ineichen claims that achieving Asymmetric Returns is the future of active asset management.